Risky Drinking Cultures Among Affluent Youth in Sweden - Hiltunen, Linda; Kvillemo, Pia; Demetry, Youstina; Gripenberg, Johanna; Elgán, Tobias H.; Skoglund, Charlotte (Frontiers in Public Health, 2022)
There is a growing scientific interest in drinking behaviour among young people in affluent areas, who report higher levels of alcohol consumption compared to youth in less privileged areas. This phenomenon has been observed in several Western countries. The research has been dominated by variable-oriented analyses and has presented interesting explanations, but there has been little research into these young people’s own experiences of and attitudes towards alcohol consumption. To develop interventions targeting this group, we need to understand their lifeworld. This study aims to develop an in-depth understanding of the high alcohol consumption among young people in affluent areas and how they themselves experience it. In the spring of 2019, we conducted 20 in-depth interviews with adolescents in upper secondary school (aged 15–19) in one of the most affluent area in Sweden. The empirical material was analysed thematically. Theoretically, the phenomenon is understood by relating to social identity processes and considering the group’s material, social and cultural means through Bourdieu’s metaphors of capital. We found that affluent youth link their social identities to alcohol consumption. Alcohol is a social beverage that opens social networks and contributes to a sense of community. The consumption of alcohol gives experience capital leading to status in this context, with clear norms and expectations governing alcohol consumption. Parties are arranged in protected spaces where young people are free to drink out of the adults’ sight. Affluent youths also have considerable purchasing power which contributes to drinking, and they are socialised into a pre-existing adult alcohol culture characterised by a liberal view on alcohol. Finally, when alcohol consumption escalates, the youths perceive that it is difficult to get adequate help from the adult world. The findings are important for future preventive interventions for subgroups of adolescents at high risk for heavy drinking.